2004
DOI: 10.1111/j.1532-950x.2004.04033.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic‐Assisted Lumbosacral Foraminotomy in the Dog

Abstract: Endoscopic-assisted foraminotomy could be used to improve intraoperative visualization in dogs with foraminal stenosis as a component of degenerative lumbosacral stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 40 publications
1
71
0
Order By: Relevance
“…Only a single previous report by Wood et al has described neurological examination after endoscopic surgery . In that study, 5 of 6 dogs had transient, slight to mild ipsilateral hind limb weakness that persisted for an average of 2 days after lumbosacral foraminotomy .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Only a single previous report by Wood et al has described neurological examination after endoscopic surgery . In that study, 5 of 6 dogs had transient, slight to mild ipsilateral hind limb weakness that persisted for an average of 2 days after lumbosacral foraminotomy .…”
Section: Discussionmentioning
confidence: 91%
“…More recently, Lockwood et al compared 2 minimally invasive approaches (i.e., foraminotomy using an illuminated port and endoscopic foraminotomy, and conventional hemilaminectomy of the thoracolumbar spinal canal), but this study also used canine cadavers . In the veterinary literature on endoscopic or endoscopic‐assisted approaches to the spine, only 1 study on live dogs has been reported . This endoscopy‐assisted surgery required an incision of at least 2 cm because it was not a full‐endoscopic procedure, which involves a totally sealed tubular approach.…”
mentioning
confidence: 99%
“…The ability to perform foramenotomy through the MI approach was not assessed in this study but would be an important factor for the utility of this approach as many dogs affected by DLSS suffer from concurrent foramenal stenosis (Wood et al 2004;Gödde and Steffen 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MI spinal surgery in humans has been reported to decrease surgical complications, blood loss, iatrogenic soft-tissue injury, as well as post-operative pain and narcotic use, and a faster return to work (Mayer and Brock 1993;Foley and Lefkowitz 2002;Topcu et al 2003). Though the discipline is more nascent in veterinary medicine, several studies have demonstrated the feasibility of MI spinal surgery and provided evidence of similar benefits (Wood et al 2004;Leperlier et al 2011;Lockwood et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A foraminotomy using endoscopically assisted instrumentation through a dorsal laminectomy can enlarge the inner part of the foramen, but the exit zone and the extraforaminal part of the L6 and L7 nerves cannot be addressed. A L7S1 traction-fusion procedure does not address extraforaminal pathologies (1, 4, 11) Moreover, the dorsolateral approach described by Gödde and Steffen allows the enlargement of the craniodorsal part of the L7 foramen, but the access is limited by the iliac wing (7). A partial, transverse iliac osteotomy removing the dorsal part of the ilium wing to increase the access has been described (12).…”
Section: Discussionmentioning
confidence: 99%